2020
DOI: 10.1101/2020.01.06.896100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myosin X interaction with KIF13B, a crucial pathway for Netrin-1-induced axonal development

Abstract: 30Myosin X (Myo X) transports cargos to the tip of filopodia for cell adhesion, migration, and neuronal axon 31 guidance. Deleted in Colorectal Cancer (DCC) is one of Myo X cargos essential for Netrin-1-regulated axon 32 pathfinding. Myo X's function in axon development in vivo and the underlying mechanisms remain poorly 33 understood. Here, we provide evidence for Myo X's function in Netrin-1-DCC regulated axon development 34 in mouse neocortex. Knocking-out (KO) or knocking-down (KD) Myo X in embryonic corti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…KIF13B has been reported to transport various cargos within cells, such as: Phosphatidylinositol 3,4,5-triphosphate (PIP3) containing lipid vesicles, low-density lipoprotein (LDL) receptor-related protein 1 (LRP1) containing vesicles, Vascular endothelial growth factor receptor 2 (VEGFR2) and Myosin X [40][41][42][43][44][45][46][47][48][49] . The molecular basis of these diverse motor-cargo interactions remains unclear, but some interactions involve the forkhead-associated (FHA) domain or MBS regions of the motor 47,55 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF13B has been reported to transport various cargos within cells, such as: Phosphatidylinositol 3,4,5-triphosphate (PIP3) containing lipid vesicles, low-density lipoprotein (LDL) receptor-related protein 1 (LRP1) containing vesicles, Vascular endothelial growth factor receptor 2 (VEGFR2) and Myosin X [40][41][42][43][44][45][46][47][48][49] . The molecular basis of these diverse motor-cargo interactions remains unclear, but some interactions involve the forkhead-associated (FHA) domain or MBS regions of the motor 47,55 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…S1). KIF13B is involved in various cellular processes, such as axon formation, neuronal cell polarity, regulation of angiogenesis, directional migration of the primordial germ cell in Xenopus embryos, the uptake of lipoproteins via endocytosis, and the transport of Rab6 secretory vesicles from the Golgi [38][39][40][41][42][43][44][45][46][47][48][49] . More recently, KIF13B has also been observed to move bidirectionally within mammalian primary cilia 50 .…”
Section: Introductionmentioning
confidence: 99%
“…Different studies reported physical binding 48, 49, 50 or functional interactions 51 between kinesin and myosin motor proteins. Dendritic spines mainly contain actin filaments 8 and myosin motors 6, 29, 42 , however depending on neuronal activity, some dynamic microtubules occasionally polymerize into dendritic spines 9, 11 and regulate cargo transport through kinesin motors, such as the KIF1A-dependent delivery of synaptotagmin IV 10 .…”
Section: Discussionmentioning
confidence: 99%